(untitled) (International Journal of Economics Management and Social Science, 2026)
Relational database design represents a foundational discipline in information systems development, requiring careful balance between theoretical rigor and practical performance considerations. This research provides comprehensive analysis of fundamental principles governing database design, focusing on normalization theory, strategic denormalization approaches, and query optimization techniques for modern database management systems. The study examines the mathematical foundations of functional dependencies and normal forms (1NF through 5NF and BCNF), analyzes trade-offs between normalized designs and performance requirements, and investigates query optimization strategies across different database architectures. Normalization theory provides systematic methodology for eliminating data redundancy and update anomalies through progressive decomposition guided by functional dependencies. However, highly normalized schemas can introduce performance penalties through excessive join operations, particularly in read-heavy applications and analytical workloads. Strategic denormalization techniques including calculated columns, materialized views, and controlled redundancy offer performance improvements while managing associated maintenance costs. Query optimization encompasses index design strategies, execution plan analysis, join algorithm selection, and database-specific optimization features. The research employs comparative methodology examining schema designs across normalization levels, measuring query performance through execution plans and actual runtime metrics, and analyzing resource utilization patterns. Results demonstrate that optimal database design requires context-specific decisions balancing data integrity, query performance, storage efficiency, and maintenance complexity. Third normal form (3NF) provides effective balance for most transactional systems, while analytical databases benefit from dimensional modeling and selective denormalization. Modern database systems increasingly support hybrid approaches combining normalized operational schemas with denormalized analytical structures. The findings provide practical guidance for database architects in making informed design decisions based on workload characteristics, scalability requirements, and consistency needs. Keywords: Relational Database, Normalization, Denormalization, Query Optimization, Database Design, DBMS, Functional Dependencies, Normal Forms